Strategic Planning of Regional Energy System Based on Life Cycle Assessment Methodology - Iosifov, Valeriy V.; Khrustalev, Evgenii Yu.; Larin, Sergey N.; Khrustalev, Oleg E. (International Journal of Energy Economics and Policy, 2020)
The Krasnodar Territory is considered one of most attractive regions in Russia in terms of its climatic characteristics for the development of renewable energy sources. According to the current plans of Russian Ministry of Energy, the cumulative capacity of wind generating facilities in the Krasnodar Territory will reach 405 MW by 2022. It is well known form the literature, the average installed capacity utilization factor of wind turbines currently is about 30%. Comparatively low installed capacity utilization factor of wind parks significantly increases their payback period, thereby reducing commercial attractiveness. However, from an environmental point of view, low installed capacity utilization factor of wind plant can also be a problem: this means that most of the energy and materials spent on the manufacturing of an energy object do not produce a useful output, in other words, wasted. Therefore, a promising way to increase the installed capacity utilization factor of wind and solar plants is the use of energy storage systems. But the production and disposal of chemical energy storage systems is also associated with significant negative environmental effects, therefore, in the case of their large-scale application it is necessary to correctly assess the environmental consequences of this method of increasing the installed capacity utilization factor of wind plants. In this study we evaluate on the basis of the LCA methodology two possible alternatives: (i) the use of wind parks without energy storage systems, and (ii) the production of energy storage systems necessary for the accumulation of electricity produced by wind parks in the Krasnodar Territory, which cannot be supplied to the power system and, hence, is thrown away. Keywords: wind energy, LCA, regional energy system, energy storage, strategic planning JEL Classifications: O33, Q42, Q47, Q48 DOI: https://doi.org/10.32479/ijeep.8791